Nucleic Acid Biology and its Application in Human Diseases - Chatterjee, Subhrangsu; Chattopadhyay, Samit (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book reviews the structure-function relationship of nucleic acids, their role in the pathophysiology of the diseases, and as therapeutic targets for human diseases. The chapters discuss the role of nucleic acids in inflammatory diseases, neurodegenerative diseases, and cancer. The book also describes recent advancements in nucleic acid-based therapy, the application of nucleic acids in diagnostics, in the development of nano-carriers, logic gates, and sensors. It explores the use of nucleic acids (RNA and DNA) as a unique and multifunctional platform for numerous applications, including therapeutics, diagnostics, nanodevices, and materials. It further examines the role of DNA methylation, histone modifiers and readers, chromatin remodelers, microRNAs, and other components of chromatin in the progression of cancer. The book also discusses the applications of nucleic acid as a vaccine and as a gene-editing tool. It also provides an overview of the clinical trials using genome editing platforms for disease treatment and the challenges in implementing the editing technology. Finally, the book elucidates a representative description of challenges associated with nucleic acid-mediated therapy.
Chapter 1_Nucleic Acid Structure and biology -- Chapter 2_Nucleic acid-mediated inflammatory diseases -- Chapter 3_ Alternative splicing and cancer -- Chapter 4_Nucleic acid-based strategies to treat neurodegenerative movement -- Chapter 5_Human Diseases induced by Oxidative damage in DNA -- Chapter 6_Nucleic Acid in Nanotechnology -- Chapter 7_ Nucleic Acid in Diagnostics -- Chapter 8_Nucleic Acid as sensors and logic gates -- Chapter 9_ Nucleic Acid Therapeutics in Cancer Biology -- Chapter 10_ Nucleic Acid as Vaccine -- Chapter 11_Nucleic Acid Editing to combat diseases.
Keywords: Diseases; Biomaterials; Nucleic acids; Cancer; Diagnosis; Diseases; Nucleic Acid; Cancers; Diagnosis